Autoimmune hepatitis and primary sclerosing cholangitis overlap syndrome in inflammatory bowel diseases - Saganek, Joanna; Meglicka, Monika; Nowakowska, Aleksandra; Osiecki, Marcin; Kierkuś, Jarosław (Pediatria Polska - Polish Journal of Paediatrics, 2023)
A close relationship between inflammatory bowel diseases (IBD) and hepatobiliary disorders, such as autoimmune hepatitis (AIH) and primary sclerosing cholangitis (PSC), is well established. Hepatobiliary manifestations occur in 30% of patients with IBD, and 5% develop chronic liver disease. The spectrum of symptoms of the overlap syndrome ranges from asymptomatic elevated liver function tests to serious diseases. The pathogenesis of liver complications in IBD is not fully recognized. It may either have an autoimmune background or be caused by intestinal inflammation, metabolic impairment, or drug toxicity. The aim of this review is to summarize AIH and PSC overlap syndrome in IBD.